Questioning inequality. Images of subaltern groups in contemporary Argentine media - Rodríguez, María Graciela (2013)
This article examines the ways in which a particular set of media representations are framed and presented in contemporary Argentina. Specifically, attention is paid to representations of socially relegated people, who are not the producers of media representations. Thus, the question of power is crucial in the setting of a fundamentally asymmetrical relationship: owners of representational production resources construct and present images and narratives of actors who do not possess these resources. Through the study of three cases, the article describes specific rhetorics that capture and aestheticize otherness in contemporary Argentina, framed in a realistic media format where the enunciation position is blurred. This element reinforces the symbolic construction of borders, through a mechanism that naturalizes and legitimizes inequality.